PENGARUH PENDEKATAN KONTEKSTUAL BERSTRATEGI REACT TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS DAN MOTIVASI BELAJAR SISWA PADA OPERASI BILANGAN BULAT - Halimatusadiah, Ai Meli Amelia; Maulana, M.; Syahid, Aah Ahmad (Jurnal Pena Ilmiah, 2017)
The low comprehension of elementary school students in integer material and the low motivation of students to learn mathematics is the background of this research. One alternative solution to the problem is to apply contextual approach REACT strategy on learning mathematics. The purpose of this study is to determine the difference between the influence of contextual approach REACT strategy compared with conventional learning on the ability of mathematical understanding and learning motivation of elementary school students on the matter of addition and reduction of integers. This study is a quasi experimental with non equivalent control group design. The results showed that both of it were able to improve the ability of mathematical understanding and learning motivation of elementary school students, but contextual approach REACT strategy was better, and there is a positive correlation between learning motivation and students mathematical understanding ability in the experimental class.